CORPOS EM CONFLITO: PODER ESTATAL, IDENTIDADE E VIOLÊNCIA EM FORÇAS ESPECIAIS (2021), DE DIAMELA ELTIT - ALMEIDA, MARIANA DE (2024)
From the 1970s onwards, some Latin American countries lived under heavy dictatorships, violent periods in which producing literature became even more difficult. At that time, writers adopted the so-called "Latin American identity", providing literature with the opportunity to bring literary aspects specific to the continent, leaving aside some colonialist traits. As a result, the combination of these characteristics helped to make Latin American literature popular and diverse, thus being able to reach the population of the countries of this continent, becoming an identity and political symbol. In this context, female writers represent a wide range of social and cultural experiences, contributing to a diverse representation of the region, and it is in this vein that we meet Diamela Eltit, author of the novel Forças Especiais (2021), which makes up the corpus of this dissertation. Analyzing this literary text, we seek to investigate how prostitution is used as a metaphor to discuss broader issues, such as power, control and resistance; analyze how the characters demonstrate resistance and resilience in the face of adversity, examining their coping strategies; understand how the identity of the protagonist character is constituted; finally, question the role of the woman's body in postmodern society, based on theoretical assumptions that discuss the concept of minor literature, identity, state power, among others. With this, it is possible to reflect on the complexities of power dynamics and the representation of prostitution, relating to the contemporary society in which we are inserted, analyzing state power and ways of resisting violence, in addition to understanding how the identity of the protagonist of the novel is constituted.